Kaidah ‘Am dalam al-Qur’an: Kajian terhadap Surat al-Ahzab Ayat 59 Serta Implikasinya terhadap Ketentuan Berhijab bagi Perempuan Muslim - Moh. Akib Muslim; Anisa Alya Rahma (Universitas Darussalam Gontor, 2024)
The commandment of hijab for Muslim women is often a significant topic in religious and social terms around the world because women are always in the spotlight in social realities. However, the obligation of hijab in QS. Al-Ahzab (33): 59 has become problematic to fashion trends. This study analyzes the rules and meanings in QS. Al-Ahzab (33): 59 and its implications for the provisions of hijab for Muslim women. This study uses thematic interpretation and content analysis methods to explore the message contained in the verse. In addition to discussing the command to use the hijab as an identity, this article also discusses QS. Al-Ahzab (33): 59 from the historical context of the verse's revelation, interpretations from various tafsir scholars, and its relevance in the modern context. The results show that the command to wear hijab in this verse aims to maintain the honor and identity of Muslim women, as well as protect them from unwanted actions. The implication of this verse on the provision of hijab emphasizes the importance of hijab as a symbol of obedience and religious identity that must be maintained by every Muslim woman. It is hoped that this research will be able to become a pivot to be studied further and in depth for further researchers.